Association between maternal micronutrient status, oxidative stress and common genetic variants in antioxidant enzymes at 15 weeks’ gestation in nulliparous women who subsequently develop pre-eclampsia - Mistry, Hiten D.; Gill, Carolyn; Kurlak, L.O.; Seed, Paul T.; Hestketh, John; Meplan, Catherine; Schomburg, Lutz; Chappell, Lucy C.; Morgan, Linda; Poston, Lucilla (Elsevier, 2015)
Aims: Pre-eclampsia is a pregnancy-specific condition affecting 2-7% of women and a leading cause of perinatal and maternal morbidity and mortality. Deficiencies of specific micronutrient antioxidant activities associated with copper, selenium, zinc and manganese, have previously been linked to pre-eclampsia at time of disease. Our aims were to investigate whether maternal plasma micronutrient concentrations and related antioxidant enzyme activities are altered prior to pre-eclampsia onset and to examine the dependence on genetic variations in these antioxidant enzymes. Methods: Pre-disease plasma samples (15+1 weeks’ gestation) were obtained from women enrolled in the international SCreening fOr Pregnancy Endpoints (SCOPE) study who subsequently developed pre-eclampsia (n=244), and age- and BMI-matched normotensive controls (n=472). Micronutrient concentrations were measured by inductively coupled plasma mass spectrometry; associated antioxidant enzyme activities, selenoprotein-P, caeruloplasmin concentrations and activities, antioxidant capacity and markers of oxidative stress were measured by colorimetric assays. Sixty four tagSNPs within genes encoding the antioxidant enzymes and selenoprotein-P were genotyped using allele-specific competitive PCR. Results: Plasma copper and caeruloplasmin concentrations were modestly, but significantly elevated in women who subsequently developed pre-eclampsia (both P<0.001) compared to controls (median [IQR], copper: 1957.4 [1787, 2177.5] vs. 1850.0 [1663.5, 2051.5] µg/L; caeruloplasmin: 2.5[1.4, 3.2] vs. 2.2[1.2, 3.0] µg/ml). There were no differences in other micronutrients or enzymes between groups. No relationship was observed between genotype for single nucleotide polymorphisms (SNPs) and antioxidant enzyme activity. Conclusions: This analysis of a prospective cohort study reports maternal micronutrient concentrations in combination with associated antioxidant enzymes and SNPs in their encoding genes in women at 15 weeks’ gestation that subsequently developed pre-eclampsia. The modest elevation in copper may contribute to oxidative stress, later in pregnancy, in those women that go on to develop pre-eclampsia. The lack of evidence to support the hypothesis that functional SNPs influence antioxidant enzyme activity in pregnant women argues against a role for these genes in the aetiology of pre-eclampsia.